2002
DOI: 10.1002/app.10815
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of oligo‐ortho‐azomethinephenol and its oligomer–metal complexes: Characterization and application as anti‐microbial agents

Abstract: ABSTRACT:The oxidative polycondensation reaction conditions and optimum parameters of o-phenylazomethinephenol (PAP) with oxygen (air) and NaOCl were determined in an aqueous alkaline solution at 60 -98°C. The properties of oligo-o-phenylazomethinephenol (OPAP) were studied by chemical and spectra analyses. PAP was converted to dimers and trimers (25-60%) by oxidation in an aqueous alkaline medium. The number average molecular weight (M n ), mass average molecular weight (M w ), and polydispersity index (PDI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…The small peak at 1677 cm À1 was attributed to the carbonyl (C ¼ O) stretching vibration, which may be formed by oxidation of the imine groups within the polymer pendent groups. 8,11 These data showed that the polymer obtained from 4-PHMP was also composed of a mixture of phenylene and oxyphenylene units.…”
Section: Structures Of 4-phmp and Poly(4-phmp)mentioning
confidence: 91%
See 1 more Smart Citation
“…The small peak at 1677 cm À1 was attributed to the carbonyl (C ¼ O) stretching vibration, which may be formed by oxidation of the imine groups within the polymer pendent groups. 8,11 These data showed that the polymer obtained from 4-PHMP was also composed of a mixture of phenylene and oxyphenylene units.…”
Section: Structures Of 4-phmp and Poly(4-phmp)mentioning
confidence: 91%
“…Thus far, the detailed polymerization behaviors of the oxidative polycondensation of NO-type phenoxy imines have been widely investigated by Kaya et al and others. [9][10][11] However, the polymerization of NNO-type phenoxy-ketimine or phenoxy-imine monomers has not yet been studied. Previously, we focused on the formation of NNO-type poly(phenoxy-ketimine).…”
Section: Introductionmentioning
confidence: 99%
“…They are promising candidates for a wide variety of applications such as optoelectronics [1,2], semiconductor [3], electrochromic [4], antistatic [5] and antimicrobial [6] materials by adding other functional groups. Efforts were focused to improve the electrooptical properties of polyphenols with longer conjugated segments.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] The Schiff base polymers demonstrate antimicrobial activity against bacteria, yeast and fungi. 17,18 Thus these can be used for the purification of industrial contaminants from heavy metals and microbiological organisms and are significant for environmental applications. These polymers are also being studied for the applications of optoelectronics.…”
Section: Introductionmentioning
confidence: 99%